2005
DOI: 10.1002/bjs.4916
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic repair of large hiatal hernias

Abstract: Background: The repair of large hiatal hernias can be technically challenging. Most series describing laparoscopic repair report only symptomatic outcomes and the true recurrence rate, including asymptomatic recurrence, is not well documented. This study evaluated the long-term outcome of laparoscopic repair of large hiatal hernias.Methods: All patients who had undergone laparoscopic repair of a large hiatus hernia (more than 50 per cent of the stomach in the hernia) with a minimum 2-year clinical follow-up we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
92
2
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(97 citation statements)
references
References 34 publications
1
92
2
2
Order By: Relevance
“…Previous reports from randomized trials 13,14,15,23 , and other studies 4,6,10 have all focussed on clinical and objective outcome parameters. However, quality of life is an alternative patient reported outcome, which reflects the general well-being and the functional status of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports from randomized trials 13,14,15,23 , and other studies 4,6,10 have all focussed on clinical and objective outcome parameters. However, quality of life is an alternative patient reported outcome, which reflects the general well-being and the functional status of patients.…”
Section: Discussionmentioning
confidence: 99%
“…These symptoms can include recurrent reflux, dysphagia, chest pain, nausea and bloating [46]. If thorough radiological assessment is performed, a recurrent HH has been defined in 15% to 42% of patients (median 22%) [1,13,36,37,41]. Wang, et al reported a prospective study looking at the clinical significance of asymptomatic recurrences and found that 35.7% of patient had a radiological recurrence [47].…”
Section: The Risk Of Recurrent Hhmentioning
confidence: 99%
“…Radiological recurrence is typically not to the same extent as the originally repaired GHH. Mostly these are small axial asymptomatic, hernias of less than 2 cm in length, of which the clinical importance is likely to be trivial [1,41]. In patients who only have recurrent reflux following a HH repair, medical management provides good symptomatic relief in the majority without ment in cardiac function [42].…”
Section: The Risk Of Recurrent Hhmentioning
confidence: 99%
See 2 more Smart Citations